Late suture site complications of sacrospinous ligament fixation. (November 2019) - Hamdy, Mostafa A.; Ahmed, Waleed A. Sayed; Taha, Omima T.; Abolill, Zakia M.; Elshahat, Amal M.; Aboelroose, Ahmed A.
Abstract: Study objective: To evaluate the late suture- related complications of sacrospinous ligament fixation (SSLF) as a treatment for uterovaginal prolapse and their impact on the quality of life. Design: A prospective cohort study. Settings: The Obstetrics and Gynecology Department of Suez Canal University Hospitals, Ismailia, Egypt from January 2014 to June 2018. Patients: We recruited sixty women with uterovaginal prolapse. Interventions: Patients underwent SSLF using the Capio suture recapturing device with non-absorbable suture material (0 braided Polyester). Postoperative visits were at six weeks then at 6, 12, 18, and 24 months after the procedure. Measurements and main results: Outcome measures were the rate and timing of suture- related and the quality of life using the pelvic floor impact questionnaire-7 at 24 months postoperatively. The mean age of the studied population was 45.7 ± 9.8 years. Suture- related complications occurred in 55% (33/60) of patients, with vaginal discharge the most commonly reported symptom. Most of them presented in the 1 st year after the procedure 72.7% (24/33), and 25% (15/60) had suture removal. However, there was a significant improvement in patients' quality of life. Conclusion: Sacrospinous ligament fixation has a positive impact on the quality of life, yet associated with significant but prominent suture- related complications.